2014
DOI: 10.1590/0103-6440201300144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Parafunctional Occlusal Loading and Crown Height on Stress Distribution

Abstract: The aim of this study was to assess, by the three-dimensional finite element method, the influence of crown-to-implant ratio and parafunctional occlusal loading on stress distribution in single external hexagon implant-supported prosthesis. Computer-aided design software was used to confection three models. Each model was composed of a block bone and an external hexagon implant (5x10.0 mm) with screw-retained implant prostheses, varying the height crown: 10, 12.5 and 15 mm. Finite element analysis software was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
(22 reference statements)
1
13
0
1
Order By: Relevance
“…The finite element analysis is usually used to assess the biomechanical behavior of situations that involve osseointegrated implants (Torcato et al 2014;Verri et al 2016Verri et al , 2017. Furthermore, the results of these studies have already been indicated for improving the biomechanical understanding of several materials or situations used in dentistry and could have their results carefully extrapolated to daily clinical (Van Staden et al 2006).…”
Section: D Analysis Configurationmentioning
confidence: 99%
See 3 more Smart Citations
“…The finite element analysis is usually used to assess the biomechanical behavior of situations that involve osseointegrated implants (Torcato et al 2014;Verri et al 2016Verri et al , 2017. Furthermore, the results of these studies have already been indicated for improving the biomechanical understanding of several materials or situations used in dentistry and could have their results carefully extrapolated to daily clinical (Van Staden et al 2006).…”
Section: D Analysis Configurationmentioning
confidence: 99%
“…Each model was composed of a bone block comprising from the first premolar to first molar, with three or two implants of external hexagon (EH) of 4.0 × 10 mm (Conexao Sistemas de Protese Ltda., Aruja, Sao Paulo, (see number of nodes and elements in the Table 1). Mechanical properties of each simulated material were attributed to the meshes using literature values (Sevimay et al 2005;Torcato et al 2014;Verri et al 2014;Santiago et al 2016) (Table 2). All materials were considered isotropic, homogeneous and linearly elastic (Verri et al 2014;Santiago et al 2016).…”
Section: Three-dimensional Fe Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical properties of the materials used in this study are listed in Table 1. A load of 100 N was applied to the crown at 45 degrees, 3 mm below the incisal edge of the lingual surface [14]. The maximal von Mises stresses in different regions and under different conditions were calculated.…”
Section: Methodsmentioning
confidence: 99%